Association of metabolic and genetic factors with cholesterol esterification rate in HDL plasma and atherogenic index of plasma in a 40 years old Slovak population - Rašlová, K; Dobiášová, M; Hubáček, J A; Bencová, D; Siváková, D; Danková, Z; Franeková, J; Jabor, A; Gašparovič, J; Vohnout, B (Physiological research, 2011)
We assessed association between novel biomarkers of cardiovascular disease and conventional factors in 40 years old subjects (208 men and 266 women) from the general population of Slovakia. FER(HDL) (cholesterol esterification rate in HDL plasma), AIP--Atherogenic Index of Plasma [Log(TG/HDL-C)] as markers of lipoprotein particle size, and CILP2, FTO and MLXIPL polymorphisms, were examined in relation to biomarkers and conventional risk factors. Univariate analyses confirmed correlation between AIP, FER(HDL) and the most of measured parameters. Relations between AIP and CILP2, FTO and MLXIPL were not significant. However, CILP2 was significantly related to FER(HDL) in both genders. In multivariate analysis BMI was the strongest correlate of AIP levels. In multivariate model variability of FER(HDL) was best explained by AIP (R(2) = 0.55) in both genders with still significant effect of CILP2 SNP in men. In a model where AIP was omitted, TG levels explained 43 % of the FER(HDL) variability in men, while in women HDL-C was the major determinant (42 %). In conclusions, FER(HDL) and AIP related to the known markers of cardiovascular risk provide means to express their subtle interactions by one number. Our novel finding of association between CILP2 polymorphism and FER(HDL) supports its role in lipid metabolism.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; Polymorphism, Single Nucleotide; Cholesterol, HDL; Humans; extracelulární matrix - proteiny; Risk Factors; prevalence; jednonukleotidový polymorfismus; Female; rizikové faktory; dospělí; lidé; Esterification; Slovenská republika; Slovakia; Extracellular Matrix Proteins; Adult; ženské pohlaví; Male; pyrofosfatasy; Genetic Predisposition to Disease; genetická predispozice k nemoci; HDL-cholesterol; Statistics as Topic; Prevalence; Risk Assessment; mužské pohlaví; statistika jako téma; hodnocení rizik; esterifikace; Pyrophosphatases